Pregnancy during the Sars-Cov-19 Pandemic (Global Journal of Medical Research, 2020)
Here we present a COVID-19 review during pregnancy, combining various factors necessary for understanding pathophysiology and susceptibility, diagnostic problems with timedomain analysis of reverse transcriptional chain reaction (RT-PCR), therapeutic inconsistencies, intrauterine response, and maternal-fetal, complications. We discuss the latest options for antiviral therapy and vaccine development, including the new use of chloroquine in the body of COVID-19. Fetal supervision, given the predisposition to growth restriction and special considerations in childbirth, is being addressed. In addition, we have provided basic services. Our clinical care model is built on the principles of segregation in the workplace, responsible social sharing, localization of cross-infection among healthcare providers, the wise use of personal protective equipment and telemedicine. Our goal is to ensure the appropriate safety of patients and healthcare providers based on it.
Keywords: pandemic; COVID-19; pregnancy; gynecology; mothercare